INTEGRASI METODE HYBRID AGILE-KANBAN UNTUK PENGEMBANGAN SISTEM PEMESANAN DENGAN TEKNOLOGI QR CODE: INTEGRATION OF THE AGILE-KANBAN HYBRID METHOD FOR THE DEVELOPMENT OF A QR CODE-BASED ORDERING SYSTEM - Muhammad Nurkholis; Acihmah Sidauruk; Melany Mustika Dewi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The growth of the culinary industry in Indonesia requires business owners to improve service quality in order to remain competitive. However, many cafes and restaurants still rely on conventional ordering systems, which often result in long queues, order recording errors, and operational inefficiencies. This study aims to develop a QR Code-based ordering system by integrating the Hybrid Agile-Kanban method as a flexible and iterative system development approach. QR Code technology allows customers to access digital menus and place orders independently via their smartphones, thereby reducing queue times and improving order accuracy. The research methodology includes needs analysis using the PIECES framework, iterative system development based on Agile principles, workflow monitoring through Kanban visualization, and usability evaluation using the System Usability Scale (SUS).A case study was conducted at De’oppra coffee Yogyakarta to demonstrate the practical implementation of the proposed system in a real business environment. The results show that the developed system achieved a SUS score of 82.6, which falls into the “Excellent” category, indicating high usability and user acceptance. These findings suggest that the integration of Hybrid Agile-Kanban with QR Code technology effectively improves service efficiency and provides a user-friendly digital ordering solution that can be adapted to various culinary businesses.